Structured search for big data : from keywords to key-objects - Gilula, Mikhail (Waltham, MA : Morgan Kaufmann, 2016)
The WWW era made billions of people dramatically dependent on the progress of data technologies, out of which Internet search and Big Data are arguably the most notable. Structured Search paradigm connects them via a fundamental concept of key-objects evolving out of keywords as the units of search. The key-object data model and KeySQL revamp the data independence principle making it applicable for Big Data and complement NoSQL with full-blown structured querying functionality. The ultimate goal is extracting Big Information from the Big Data. As a Big Data Consultant, Mikhail Gilula combines.
Note continued: 7.3.3. KeySQL on MapReduce Clusters -- 7.4. Structured Search in Internet Evolution -- 7.4.1. Internet as Data Store.
Vendor-supplied metadata.
Keywords: Big data; Internet searching; Database searching; Keyword searching; COMPUTERS -- General; COMPUTERS -- Database Management -- General; Big data; Database searching; Internet searching; Keyword searching; Electronic book; Electronic books